2018
DOI: 10.1182/blood-2018-99-112599
|View full text |Cite
|
Sign up to set email alerts
|

Updated Analysis of the Efficacy and Safety of Tisagenlecleucel in Pediatric and Young Adult Patients with Relapsed/Refractory (r/r) Acute Lymphoblastic Leukemia

Abstract: BACKGROUND Tisagenlecleucel is an FDA approved chimeric antigen receptor (CAR)-T cell therapy that reprograms T cells to eliminate CD19+ B cells. ELIANA (NCT02435849) is a phase 2 pivotal study of tisagenlecleucel in pediatric/young adult patients (pts) with CD19+ r/r B-cell acute lymphoblastic leukemia (ALL), the first global trial of a CAR-T cell therapy. The primary objective was met, with an overall remission rate (ORR) of 81% (complete remission [CR] + CR with incomplete blood count recover… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
101
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(108 citation statements)
references
References 0 publications
5
101
0
Order By: Relevance
“…These data, along with those from previous studies, demonstrate the potential of CAR T-cells for treating leukemia, especially ALL (6,13,14).…”
supporting
confidence: 81%
“…These data, along with those from previous studies, demonstrate the potential of CAR T-cells for treating leukemia, especially ALL (6,13,14).…”
supporting
confidence: 81%
“…Efficacy As of 2018, 97 patients aged ≤21 years with r/r ALL were enrolled in the ELIANA trial, 79 patients were infused with CD19 CAR T cells and a complete remission was achieved in 65 patients. After a median followup of 24 months, response was ongoing in 29 patients (45%), with a maximum (ongoing) duration of response of 29 months [77]. For r/r DLBCL patients treated with tisagenlecleucel, the updated analysis presented at EHA 2018 included 111 infused patients.…”
Section: Chimeric Antigen Receptor T Cellsmentioning
confidence: 99%
“…The generation of CAR T cells to treat B-ALL is a significant advancement in the field. 136,[180][181][182] The treatment of patients with CAR T cells has served as a bridge for transplant, enabling patients who were formerly unable to receive a transplant due to poor remission status to achieve a CR and ultimately transplantation. It is also reported that patients who received CAR T cells can maintain longterm remission without subsequent HSCT.…”
Section: Car T Cellsmentioning
confidence: 99%